Pattern of Antimicrobial Sensitivity of Organisms Causing Urinary Tract Infection in Nephrotic Syndrome in Children (Bangladesh Journal of Child Health, 2017)
Background: Urinary tract infection (UTI) is a common infection in nephrotic syndrome children having a propensity for long term renal damage. Organisms causing UTI in nephrotic syndrome are becoming resistant to common antimicrobial agents and increase the morbidity and mortality. Surveillance of local antibiotic sensitivity pattern is necessary for proper management of UTI in nephrotic children.Objective: To see the pattern of antimicrobials sensitivity of organisms causing UTI in Nephrotic syndrome children.Methods: This was a hospital based cross-sectional study conducted in the department of Paediatrics, Chittagong Medical College Hospital, Chittagong from January 2009 to December 2009. 52 nephrotic children aged 2-6 years with typical clinical features were included. A clean catch midstream urine sample were collected in aseptic procedure and sent for inoculation in culture media. In case of collection failure, urine was collected by sterile catheterization. Bacterial isolates were tested for microbial sensitivity. Data regarding etiological organisms and antibiogram were analyzed using appropriate statistical method.Results: UTI was found in 30.8% nephrotic children. E-coli was the commonest organism isolated in urine culture followed by klebsiella. All organisms isolated on culture were more or less resistant to commonly used antibiotics except to amikacin. E coli were resistant to most of antibiotics and resistance to cotrimoxazol is quite high for all isolates. Ciprofloxacin as oral and amikacin as parenteral are good for first line treatment of UTI in nephrotic syndrome.Conclusion: Resistance among organisms causing UTI in nephrotic syndrome is an emergent problem now a day. Routine urine culture should be advised since treatment failure is likely to occur with commonly used antibiotics. Risk factor for emergence of antibiotic resistance of these pathogens should be evaluated.Bangladesh J Child Health 2016; VOL 40 (3) :154-159